2015
DOI: 10.1021/acs.macromol.5b01089
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Main-Chain Configuration on the Mechanical Properties of Linear Aliphatic Polyesters

Abstract: Linear aliphatic polyesters have been investigated extensively over the last decades. However, the relation between the configuration of the ester groups in the main chain and the mechanical properties is only poorly understood. Therefore, in this work the influence of the composition of these polymers on the morphology, mechanical properties and relaxation processes for a set of random copolymers of ε-caprolactone (CL) and ω-pentadecalactone (PDL) is explored. For these isomorphic copolymers, the crystallinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 49 publications
4
33
1
Order By: Relevance
“…Concerning the high temperature/low strain rate process I, plastic deformation of the crystalline lamellae through a crystallographic slip mechanism was previously proposed as the underlying mechanism . Remarkably, however, the results presented here for the different polymorphs seem to disagree with this interpretation.…”
Section: Resultscontrasting
confidence: 67%
See 1 more Smart Citation
“…Concerning the high temperature/low strain rate process I, plastic deformation of the crystalline lamellae through a crystallographic slip mechanism was previously proposed as the underlying mechanism . Remarkably, however, the results presented here for the different polymorphs seem to disagree with this interpretation.…”
Section: Resultscontrasting
confidence: 67%
“…The yield stress of polymers depends strongly on loading conditions and, in the case of semicrystalline polymers, it depends on structural features like crystallinity or lamellar thickness as well . Furthermore, imperfections in the crystal lattices can have a pronounced effect . It is difficult to draw clear conclusions on the effect of these distinct structural features, since it is hard to vary single features without affecting others.…”
Section: Resultsmentioning
confidence: 99%
“…A later study with AFM directly imaged the lamella thicknesses, in good agreement with the SAXS measurements. 49 In contrast, a study of linear aliphatic polyesters consisting of E-caprolactone (CL) and x-pentadecalactone (PDL) 50 indicated that, up to 80% CL units could be incorporated within the PDL lattice without loss of crystallinity and with constant lamellar thickness. Contrary to the PET/PEN system however, the authors considered that in the CL/PDL system the CL units are incorporated within the PDL crystal structure without the need for sequence matching.…”
Section: Crystallization Morphologymentioning
confidence: 99%
“…34 In the framework of our interest in the ROP of macrolides, we wish to report the achievement of the homo-and copolymerization of 6HDL with ω-PDL and CL in the presence of a pyridylamidozinc(II) complex, which has been recently described by some of us for the copolymerization of CO 2 and epoxides 35 and for the block copolymerization of CL and lactides. 36 The copolymerization of ω-PDL with other lactones, having conventional ring-size, has been already described in the literature 27,[37][38][39][40][41][42][43][44] to give both block and random copolymers. Conversely, the copolymerization of other macrolactones, such as ethylene brassilate, with smaller lactones was also described in the literature.…”
Section: Introductionmentioning
confidence: 99%